Impact of STEM Professional Development Sessions on Chinese Pre-service Early Childhood Teachers - Stonier, Francis; Adarkwah, Michael Agyemang (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
STEM only recently became part of the official Chinese public school curriculum in 2017 and suggested to be included in the primary school curriculum in 2018. This study shares findings from 79 Chinese pre-serivice early childhood teachers participating in a variety of hands-on STEM activities over a two week period. A follow-up question session was conducted with the translator as well. This training was offered outside of normal class times as a professional development. Data showed significant differences between the pre- and post- surveys along with strong relationships between main categories. Indications are that the sessions helped to promote the participant’s interest, perception, self-efficacy in STEM, as well as, thoughts toward STEM/science teachers and classes in their current program. Findings most strongly indicated that the sessions aided understanding of STEM and that STEM could be fun in terms of both learning and teaching. Overall, it appeared that the professional development sessions were meaningful for the participants and highlighted STEM practices and concepts in a positive light.